Estimating the spatial distribution of urban heat islands in six central districts of Ulaanbaatar city using machine learning algorithm (Mongolian Journal of Geography and Geoecology, 2025)
Urban Heat Islands (UHIs) represent a growing environmental challenge in rapidly urbanizing cities, particularly in extreme climate regions such as Ulaanbaatar, Mongolia. This study aims to model and analyze the spatial distribution of UHIs across six central districts of Ulaanbaatar using Landsat 5 and Landsat 8 satellite imagery. Land Surface Temperature (LST) was derived from Landsat 8, and its relationship with six spectral indices the Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), Modified Normalized Difference Water Index (MNDWI), Bare Soil index (BI), Normalized Differences Water Index (NDWI), and Normalized Building Soil Index (NDBSI) was assessed. Two ensemble machine learning algorithms, Random Forest (RF) and Extreme Gradient Boosting (XGB), were employed to model UHI patterns. RF performed better in 1994 (a coefficients of determination (R²) = 0.72, a root-mean-square error (RMSE) = 1.89°C), while XGB showed superior performance in 2024 (R2 = 0.75, RMSE = 1.97°C). BI and NDBSI were the most influential contributors to UHI intensity, whereas vegetated areas (NDVI, MNDVI) had consistent cooling effects. The spatial modeling revealed a clear intensification of UHI effects over time, particularly in built-up and bare land zones. This study is significant as it applies ML techniques to long-term satellite data in a cold-climate, data-limited urban setting. By providing a rare longitudinal perspective, it contributes to understanding UHI dynamics in Mongolia and demonstrates the potential of open-access remote sensing data combined with ML for urban climate assessments. The findings offer valuable insight for urban planners, emphasizing the critical role of green infrastructure in mitigating thermal stress and informing climate-resilient development strategies in rapidly growing cities.